Perubahan sifat-sifat fisik dan mekanik kayu kemiri (Aleurites moluccanus (L.) Willd.) setelah perlakuan pemanasan dengan minyak [Changes of physical and mechanical properties of candlenut wood (Aleurites moluccanus (L.) Willd.) after oil-heat treatment] - Arjun Azis; A. Detti Yunianti; Agussalim Agussalim (Jurnal Riset Industri Hasil Hutan, 2021)
Candlenut wood is one of low quality wood species in term of strength and durability class of V-IV, so its utilization is limited. Efforts to improve physical and mechanical properties of wood are required. One way is using wood modification technology by oil-heat treatment. This research aim was to analyze the changes in physical and mechanical properties of candlenut wood after heating with oil. The stages of this research were sample pre-treatment, heating treatment and wood testing. Samples were pre-treated by heating gradually at 60°C and 90°C for 24 hours to avoid crack during treatment. The heat treatment was applied at several variation of temperatures, namely (160, 180, and 200)°C for 1 and 2 hours, respectively. Properties of wood were tested according to modified ASTM D143-94 standard. The Completely Randomized Design was used to determine effect of heat temperature and time on the wood properties. The results showed that heating with oil on candlenut wood gave a positive response, as evidenced by an increase in physical and mechanical properties of wood. Oil-heat treatment could be an effective method for improve properties of  wood. The increases of specific gravity, MOE and MOR were ranged from (16.49 to 26.62)%, (1.25 to 13.61)%, and (4.37 to 10.15)%, respectively. The use of 160°C increased properties of wood with relatively higher compared to other temperatures in 1 hour. Longer heating times tend to reduce properties of wood.